PENGGUNAAN BAHASA INGGRIS DALAM PERCAKAPAN PRAMUSAJI PADA KANAL YOUTUBE - I Nyoman Muliana; I Gusti Ayu Agung Dian Susanthi; A.A.Istri Manik Warmadewi; I Made Astu Mahayana (Universitas Warmadewa, 2025)
This research aims to analyze the conversational structures used by waiters in videos uploaded to YouTube channels. This research focuses on using English in restaurant service and its relationship with the tourism industry using digital technology. The research data was obtained from videos uploaded by YouTubers showing waiters' activities, particularly their communication with customers. The phenomenological method, a qualitative approach, was used in this study. The data collected was analyzed through transcription to find the conversational structures used. The results show that waitresses use English terms for various purposes, such as greeting, requesting information, and informing others. These phrases usually use a formal style that shows the service's professionalism. In addition, the conversations found show organized and effective communication techniques. This can be a learning reference for tourism industry players and people who want to improve their English skills. This study found that the effective use of English in the tourism industry is very important, especially in improving the quality of communication and service. This study also helps develop sociopragmatic research in digital communication and suggests further research to investigate interaction patterns on other social media platforms.